The Impact of Capital Structure on Firm Performance: A Case Study on ASEAN Countries - Saidakhmatov Sarvarbek Sirojiddin Ugli; Indah Fitriani; Alfira Sofia; Umarova Zulayxo Turzunovna (CV. Tripe Konsultan, 2026)
This study examines the impact of capital structure on firm performance using panel data from ASEAN countries between 2019 and 2023. The sample consists of publicly listed non-financial firms in emerging markets, enabling an evaluation of how leverage influences profitability under varying regulatory and financial environments. Firm performance is measured using return on assets (ROA) and return on equity (ROE), while capital structure is proxied by debt-to-equity and debt-to-assets ratios. Panel regression methods are employed to control for firm-specific heterogeneity and macroeconomic factors.The findings suggest that higher leverage does not necessarily improve profitability; instead, firms with greater debt levels may experience reduced performance. However, this relationship is non-linear and depends on the extent of leverage and its impact on earnings. The results support the trade-off theory in the ASEAN context, emphasizing the importance of maintaining an optimal capital structure. These findings provide practical implications for corporate managers and policymakers in formulating balanced financing strategies to enhance financial stability and long-term performance.